Towards a valid Afrikaans-translation of the CASr-SF: a linguistic and cultural transfer - Steyn, Constanze (Rhodes University, Faculty of Humanities, Department of Psychology)
Globally, and especially in South Africa, we face the reality of linguistic and cultural variation within one nation. Our nation is intricately woven from rich cultural and linguistic threads to create a complex tapestry. It is a beautiful privilege that is, however, not without its obstacles. We often do not have access to psychometric tools that "speak" the language of the respondent that we intend to assess. It is, and should, however, be, our goal to adapt and translate assessments to allow individuals to convey their experience in their language of comfort. This is crucial for psychological assessments' fairness, reliability, validity, and utility. Intimate partner violence (IPV) severely impacts mental health worldwide. An alarming correlation has been found between exposure to IPV and the development of mental health difficulties. In South Africa, IPV is considered a significant public health issue. Even though South Africa has a population of approximately 60,9 million, of whom an estimated 10.6% are Afrikaans-speaking, there is currently no measure exploring the experiences of IPV available in Afrikaans. Having psychological assessments available in Afrikaans is essential in evaluating the psychological experiences of people seeking mental health services in Afrikaans. The Composite Abuse Scale (Revised) "“ Short Form (CASr-SF) is a self-report questionnaire that measures experiences of IPV across three domains: physical, psychological, and sexual abuse. This study aimed to develop a meaningful and relevant Afrikaans translation of the CASr-SF to improve the linguistic accessibility of the measure and afford more ease to Afrikaans-speaking individuals in sharing experiences of abuse. This study followed a four-step translation design, including forward- and backtranslation, a committee approach, and qualitative piloting through cognitive interviews. Participants in this study included four independent translators who were approached by the researcher directly, according to their respective areas of expertise "“ linguistics and psychology. In addition, three participants were sourced from the target population through snowball sampling to partake in cognitive interviews as a confirmatory step and to potentially substantiate, expand on, and review results gathered during the first three steps of the translation design. The researcher ii compared, collated, and analysed the data to identify problematic items. The translation team then discussed these items to refine the translation, and items were corrected to develop the final translation of the Composite Abuse Scale (Revised) "“ Short Form in Afrikaans. The translation is now ready for quantitative piloting, which is currently underway to establish its psychometric properties.
Keywords: Intimate partner violence -- South Africa; Afrikaans language; Psychological tests Translating; Psychometrics; Victims of family violence Mental health